An efficient and secure linear diffusion layer for 256-bit block cipher based on FLC structure - Nam, Trần Sỹ; Long, Nguyễn Văn; Cương , Nguyễn Bùi (Journal of Science and Technology on Information security, 2023)
Abstract— In this paper, we propose a secured and efficient linear diffusion layer that suitable for block cipher with 256-bit block size named FLC. Specifically, we have generated an 8×8 MDS matrix that has the power of a companion matrix over a finite field. We also perform a performance evaluation of the encryption/decryption process on various platforms. Our experimental results show that block cipher with our proposed linear diffusion layer is perfectly suitable for real life applications.